2012
DOI: 10.1111/j.1471-0307.2012.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of refrigerated storage of raw milk on the physicochemical and microbiological quality of Tunisian semihard Gouda‐type cheese during ripening

Abstract: A Tunisian semihard Gouda‐type cheese made from milk kept at 4 °C for 24, 48, 72 and 96 h was monitored during 45 days of ripening. The effect of milk refrigeration on the evolution of physicochemical parameters in relation to the quantitative variation of the microbial population during ripening of Gouda‐type cheese was investigated. Microbiological and physicochemical analyses were performed on raw milk and cheese samples after curding, 2, 9, 16, 23, 30, 37 and 45 days of ripening time. The raw milk kept und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Another technological problem in the dairy industry caused by proteolytic activity from psychrotrophic microorganisms is the yield reduction in cheese manufacturing ( Cardoso, 2006 ; Mankai et al, 2012 ). Cardoso (2006) showed a reduction of 6.38% in total solids in fresh Minas cheese produced using a raw milk stored for four days under cold temperatures, which promotes psychrotrophic growth.…”
Section: Heat-stable Spoilage Enzymes Produced By Psychrotrophic Micrmentioning
confidence: 99%
“…Another technological problem in the dairy industry caused by proteolytic activity from psychrotrophic microorganisms is the yield reduction in cheese manufacturing ( Cardoso, 2006 ; Mankai et al, 2012 ). Cardoso (2006) showed a reduction of 6.38% in total solids in fresh Minas cheese produced using a raw milk stored for four days under cold temperatures, which promotes psychrotrophic growth.…”
Section: Heat-stable Spoilage Enzymes Produced By Psychrotrophic Micrmentioning
confidence: 99%
“…A reduction in cheese yield and tainting are the two most frequently reported negative effects in cheese production that are attributed to psychrotrophic-derived enzymes ( Mcphee and Griffiths, 2011 ). Less frequently reported effects include the alteration of starter activity and/or growth rates and rennet coagulation times ( Datta and Deeth, 2001 ; Mankai et al , 2012 ). Reduced yields in cheese production occur mainly because soluble casein degradation products (peptides and amino acids) may be lost into the whey instead of forming part of the curd ( Mcphee and Griffiths, 2011 ).…”
Section: Psychrotrophic Bacteria In Milkmentioning
confidence: 99%
“…Reduced yields in cheese production occur mainly because soluble casein degradation products (peptides and amino acids) may be lost into the whey instead of forming part of the curd ( Mcphee and Griffiths, 2011 ). The tainting problems are due to the action of proteases, which generate bitter flavours, and lipases, which hydrolyse milk fat yielding free fatty acids (FFAS) and generate strong flavours that in the majority of cases are considered undesirable ( Deeth, 2006 ; Mankai et al , 2012 ).…”
Section: Psychrotrophic Bacteria In Milkmentioning
confidence: 99%
“…In addition, pasteurization is used to reduce the microbial load of milk, but the lysis of psychrotrophic bacteria may lead to the release of heat resistant proteolytic and lipolytic enzymes that could affect the shelf life of milk and dairy products such as cheeses and milk powders. A previous study showed that heat-resistant proteolytic enzymes from psychrotrophic bacteria could result in the degradation of cheese caseins, resulting in a reduced cheese yield (Mankai et al, 2012); whereas another report showed that raw goat milk should not be stored for more than 3 d at 4°C after heat treatment or the presence of lipolytic enzymes will reduce the quality of milk powder, which typically has a shelf-life of 180 d (Fonseca et al, 2013). In addition, gram-positive spore-forming bacteria are also known to contribute to milk spoilage, as they may survive heat treatments and become a dominant population within the microflora of pasteurized milk (Ranieri et al, 2009).…”
Section: Introductionmentioning
confidence: 99%